Myeloid but not hepatocytic CD38 is a key driver for hepatic ischemia/reperfusion injury - Qi-Hang Zhao; Ya-Ting Zhang; Ke Wen; Qi Ding; Zi-Ying Chen; Dilinuer Tula; Jia-Hui Li; Juan Zhou; Yun-Fei Xiao; Xiao-Hui Guan; Ke-Yu Deng; Ling-Fang Wang; et al. (Signal Transduction and Targeted Therapy)
Abstract Hepatic ischemia-reperfusion injury (HIRI) is a critical condition that often occurs during liver transplantation and surgical liver resection. However, its mechanism has not been fully elucidated. Nicotinamide adenine dinucleotide (NAD+), functioning as a coenzyme or cofactor, is crucial for both redox and non-redox processes. In mammals, CD38 serves as the primary enzyme responsible for NAD+ degradation. In this study, we reported that the absence of CD38 markedly reduces HIRI in CD38 global knockout (CD38KO) and CD38 myeloid-specific knockout (CD38MKO) mice, but not in CD38 hepatocyte-specific knockout (CD38LKO) mice compared with the control (CD38fl/fl) mice by suppressing HIRI-induced hepatic oxidative stress, inflammatory responses, and pyroptosis. The findings were corroborated by a noticeable decrease in levels of alanine aminotransferase (ALT), aspartate transaminase (AST), and lactate dehydrogenase (LDH), along with reduced necrosis. Besides, we found that the expressions of SIRT1 and its downstream targets, p53 and PPARγ, were elevated in the liver tissues of CD38KO and CD38MKO mice compared to CD38fl/fl mice, while the acetylation levels of p53 were reduced. Furthermore, we demonstrated that myeloid CD38 deficiency not only promoted M2-type polarization and inhibited M1-type polarization of macrophages but also suppressed NLRP3-mediated pyroptosis by triggering NAD+/SIRT1 signaling in macrophages, resulting in the reduction of oxidative stress, inflammation, and pyroptosis in the liver, ultimately protecting against HIRI. This study highlights myeloid CD38 as a promising target for the prevention and treatment of HIRI clinically.